Decision in the Case of nullitatis matrimonii on the Grounds of the Exclusion of the Indissolubility of Marriage (can. 1101 § 2 CIC) and, subordinate on the Grounds of Error Concerning a Quality of the Person (can. 1097 § 2 CIC), on the Part of the Plaintiff, in the Judgment of the Roman Rota coram Todisco, of 27 September 2017 - Góralski, Wojciech (Prawo Kanoniczne, 2025)
The author presents the judgment of the Roman Rota, coram Todisco, dated 27 September 2017, concerning a case brought by a woman before the Interdiocesan Tribunal seeking the declaration of the nullity of her marriage on the grounds of her own exclusion of the indissolubility of marriage. In formulating the dubium, the Tribunal considered the woman’s exclusion of the indissolubility of marriage (can. 1101 §2 CIC) and – subordinately – her error concerning a quality of the person (can. 1097 §2). After issuing a positive judgment on the ground of error qualitatis, the respondent lodged an appeal (together with a petition for nullity of the judgment) before the Roman Rota, where the panel of judges, coram Todisco, declared the marriage null and void solely on the ground of the petitioner’s exclusion of the indissolubility of marriage.